Coda - Lim, Zi Yu (2019)
This essay showcases my learning journey as a Producer for my undergraduate thesis film, Coda; and a brief report on my secondary role as an Art Director for When the Night Falls. I would like to thank Professor Chul Heo and Professor Ross Williams for their kind guidance, and for meeting up with me whenever I request for, and for always giving me advices on how to deal with certain situations and grow. I would also like to thank Mr Abdul Shukor, Mr Arifin and Mr Wee Liang for the tremendous technical support and facilities booking for my team and I. Lastly, I would like to express my greatest gratitude to my understanding family and friends, who have not given up on me despite my busy schedule and slow responding messages; hold on everybody, I am coming home.